Beyond Life-Death Dualism: The Buddhist Conception оf Existence - Budriūnaitė, Agnė (Problemos, 2004)
The “ordinary” person of Western society does not recognize his or her death as unavoidable future, tries to forget it and lives as if his or her existence would be life-without-death. Everyday life presents its evidences of human fragility and temporality. Such person tries to strengthen his or her ‘Self’ more and more in order to overcome death anxiety. The existentialists noticed that recognition of one’s own death as the inseparable part of existence makes human being more authentic, free and conscious. One, who has acknowledged the inescapable interconnection between life and death, has two alternatives. To accept death as intrinsic essence of life (death-in-life) and live with the existential anxiety; or to measure life and death by dimensions of eternity and to look forward to eternal life without fear of death (life-in-death). The buddhism offers another way of thinking by equalizing life and death and showing the illusiveness of ‘Self’. The buddhist term suunyataa may seem identical to Nothingness in existentialist philosophy, but it is not. M. Heidegger is the only philosopher, whose ideas may be compared to Buddhism, in spite of very different buddhist interpretation of his philosophy. Buddhism finds the most intimate and resembling accordance in German mysticism and particularly in negative theology of Meister Eckhart. Only after refusing all attachments to the world and oneself the soul can reach Godness. The life and death dualism as well as the delusive ‘Self’ or ‘Ego’ disappears in the presence of suunyataa or God as Eckhart understands it or Nothingness as M. Heidegger reflects on it.
Keywords: existence; buddhism; death; emptiness; nothingness.